2017
DOI: 10.1080/19420862.2017.1336592
|View full text |Cite
|
Sign up to set email alerts
|

Design, development and characterization of ACT017, a humanized Fab that blocks platelet's glycoprotein VI function without causing bleeding risks

Abstract: Glycoprotein VI is a platelet-specific collagen receptor critical for in vivo formation of arterial thrombosis. It is also considered as an attractive target for the development of anti-thrombotic drugs because blocking glycoprotein (GP)VI inhibits platelet aggregation without inducing detrimental effects on physiologic hemostasis.Here, we present data on the identification, in vitro and ex vivo pharmacology of a humanized Fab fragment designated as ACT017. ACT017 was selected out of 15 humanized variants base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 59 publications
(42 reference statements)
4
58
0
1
Order By: Relevance
“…Consistent with observations made in GPVI‐deficient patients, inhibition, immunodepletion, or genetic deletion of GPVI in animals only had minor consequences on primary hemostasis . In contrast to its limited impact on primary hemostasis, GPVI deficiency conferred remarkable protection against thrombosis in a variety of in vitro and in vivo experimental models, including flow chamber‐based assays using human atherosclerotic plaque material . For these reasons, and despite some controversies, GPVI has been proposed as a promising target for antithrombotic therapy with reduced bleeding risk as compared to current antiplatelet therapies based on administration of aspirin and/or P2Y12 inhibitors …”
Section: Gpvi In Primary Hemostasis and Thrombosissupporting
confidence: 56%
See 1 more Smart Citation
“…Consistent with observations made in GPVI‐deficient patients, inhibition, immunodepletion, or genetic deletion of GPVI in animals only had minor consequences on primary hemostasis . In contrast to its limited impact on primary hemostasis, GPVI deficiency conferred remarkable protection against thrombosis in a variety of in vitro and in vivo experimental models, including flow chamber‐based assays using human atherosclerotic plaque material . For these reasons, and despite some controversies, GPVI has been proposed as a promising target for antithrombotic therapy with reduced bleeding risk as compared to current antiplatelet therapies based on administration of aspirin and/or P2Y12 inhibitors …”
Section: Gpvi In Primary Hemostasis and Thrombosissupporting
confidence: 56%
“…42,43 In contrast to its limited impact on primary hemostasis, GPVI deficiency conferred remarkable protection against thrombosis in a variety of in vitro and in vivo experimental models, including flow chamber-based assays using human atherosclerotic plaque material. 27,33,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] For these reasons, and despite some controversies, GPVI has been proposed as a promising target for antithrombotic therapy with reduced bleeding risk as compared to current antiplatelet therapies based on administration of aspirin and/or P2Y12 inhibitors. 42,43 The mild bleeding manifestations in patients with GPVI deficiency suggest that either GPVI plays a modest role in hemostasis or, more likely, that its absence is overcome by compensatory and/ or redundant mechanisms.…”
mentioning
confidence: 99%
“…We also successfully engineered a PpL binding motif in order to make the purification of antibody fragments using affinity chromatography possible, without requiring the insertion of an epitope tag. This strategy is essential considering future pharmaceutical developments [38][39][40]. The monomeric scFv was produced in bacteria and characterized from a physico-chemical point of view.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the affinity for the toxin and potentially the non-optimal thermal stability we observed for scFv 15 hLi7 could be related to some of the mutations that also altered the VH/VL packing angle. Recent studies have shown that a high degree of cooperation between the VH/VL is required for mutual stabilization and also that a limited number of residues buried inside the antibody domain are critical to maintain the topography of the antigen-binding site [25,39,60]. The mutation H80 A > R slightly impacts the canonical H2 conformation.…”
Section: Discussionmentioning
confidence: 99%
“…When re-engineering variable domains, affinity maturation and antibody humanization are carefully considered and worked on [11][12][13][14][15][16]. In some cases, mutations in the antibody complementarity determining regions (CDRs) have shown to improve molecule stability [17,18] thus being able to repair intrinsic flaws in the packing between two V-domains [19].…”
Section: Introductionmentioning
confidence: 99%